2012
DOI: 10.1016/j.sdentj.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure time on the accuracy and reliability of cone beam computed tomography in the assessment of dental implant site dimensions in dry skulls

Abstract: In imaging of dry skulls, lowering the CBCT exposure time from 40 s to 20 or 7 s does not affect the reliability or accuracy of implant site measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…3,5 No randomized controlled trials were found during the literature search. Of the 22 other full-text articles included in the review, 10 studies looked at the effect of altering the current, [19][20][21][22][23][24][25][26][27][28] 6 studies at altering kilovoltage 19,20,23,24,26,27 and 18 studies at altering exposure time factors 19,21,22,[24][25][26][27][29][30][31][32][33][34][35][36][37][38][39] (some studies looked at more than one exposure parameter, so this total equals .20 studies). One study 40 investigated the combined effect of current and exposure times on image quality by altering mAs values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5 No randomized controlled trials were found during the literature search. Of the 22 other full-text articles included in the review, 10 studies looked at the effect of altering the current, [19][20][21][22][23][24][25][26][27][28] 6 studies at altering kilovoltage 19,20,23,24,26,27 and 18 studies at altering exposure time factors 19,21,22,[24][25][26][27][29][30][31][32][33][34][35][36][37][38][39] (some studies looked at more than one exposure parameter, so this total equals .20 studies). One study 40 investigated the combined effect of current and exposure times on image quality by altering mAs values.…”
Section: Resultsmentioning
confidence: 99%
“…5 different types of reference standard were described across the 11 studies which measured diagnostic accuracy. 20,25,27,29,30,[32][33][34][36][37][38] In addition, of these 22 studies, 17 studies reviewed how altering exposure parameters affected the image quality of scans produced for specific diagnostic tasks (Table 1), while 5 studies looked at a range of CBCT exposure protocols which could have been used for several diagnostic tasks. 19,23,29,31,40 Across the total 22 studies reviewed, 23 different names were given for CBCT machines used in the research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20] Most of these have been aimed at the use of CBCT in implant dentistry, while others have investigated the impact on diagnosis of simulated root resorption and periapical pathosis. Only two studies have specifically looked at orthodontic-related applications of CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that there is scope for reducing exposure factors without loss of adequate image quality in various clinical contexts. [9][10][11][12][13][14][15][16][17][18][19][20] Low-dose protocols are a familiar optimization strategy for "medical" CT, 21 but there is almost no comparable literature related to dental CBCT. The impact of low-dose scanning protocols on objective measurements of image quality, available on one CBCT machine, has been assessed, 22 but this study did not include a subjective image quality assessment of clinical images.…”
Section: Introductionmentioning
confidence: 99%